THE ENDEMIC TRANSMISSION MODEL OF BULIMIA NERVOSA - Priyantini Putri, Artin
Bulimia nervosa is one of the eating disorder which have big effect for young woman in age between 15-25 years old in USA. This final project will construct a mathematical model which govern the spread of Bulimia and will use the modification of the SIR (Susceptible, Infected, Recovery) model. There are two models, one is Bulimia with Anorexia, and the other one is Bulimia without Anorexia (Two stage Bulimia model). In the Bulimia-without-Anorexia model, there are four compartments: ???? (Susceptible), ????1 (Closet Bulimia), ????2 (Advanced Bulimia) and ???? (Treatment) and for Bulimia-with-Anorexia model, six compartments will be used. Analysis and numeric simulation will be applied for these two models in order to know which parameters play a big role in spreading the bulimia so that the spreading of Bulimia can be stopped.